Effect of Cassava Biogasoline on Fuel Consumption and CO Exhaust Emissions - Mujahid Wahyu; Hadi Rahmad; Gabriel Jeremy Gotama (Automotive Experiences, 2019)
Cassava biogasoline was tested on electronic fuel injection vehicles in urban traffic conditions with varying engine load. Biogasoline tested includes B0, B10, B20, and B30. The engine speed was operated within 750 to 1800 rpm (low-speed range) to simulate urban traffic condition. The engine load was varied through the operation of air conditioner (AC). Fuel consumption was measured in real terms (ml/s) and CO emissions were measured with the Hesbon HG 520 Engine Gas Analyzer (EGA) in the percentage of total exhaust gas. The results showed that B10 has the lowest fuel consumption of 0.24 ml/s in conditions without AC and 0.41 ml/s with AC. Meanwhile, CO emissions tend to be constant with change in the proportion of cassava biogasoline and increased with additional AC load.